Continuous Enhancement of Science Teachers’ Knowledge and Skills through Scientific Lecturing - Azevedo, Maria-Manuel; Duarte, Sofia (Frontiers in Public Health, 2018)
Introduction: Due to their importance in transmitting knowledge, teachers can play a crucial role in students' scientific literacy acquisition and motivation to respond to ongoing and future economic and societal challenges. However, to conduct this task effectively, teachers need to continuously improve their knowledge, and for that a periodic update is mandatory for actualization of scientific knowledge and skills. This work is based on the outcomes of an educational study implemented with science teachers from Portuguese Basic and Secondary schools. We evaluated the effectiveness of a training activity consisting of lectures covering environmental and health sciences conducted by scientists/academic teachers. Material and methods: The outcomes of this educational study were evaluated using a survey with several questions about environmental and health scientific topics. Responses to the survey were analyzed before and after the implementation of the scientific lectures. Results: Our results showed that Basic and Secondary schools teachers' knowledge was greatly improved after the lectures. The teachers under training felt that these scientific lectures have positively impacted their current knowledge and awareness on several up-to-date scientific topics, as well as their teaching methods. Learning outcomes: This study emphasizes the importance of continuing teacher education concerning knowledge and awareness about health and environmental education.